The Effect Of The Application Of The Use Of Google Classroom As A Learning Media At SMA Negeri 1 Pancur Batu - Arafah, Andini; Mawaddah, Ikra; Saleh, Saleh; hasan batubara, Mukhtar (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
In today's era, technological developments are very fast so that they can support learning very well, for example using the classroom application where using this application can make it easier for educators and students to carry out the learning process, where in this classroom application you will be able to send files, videos, links , ppt and so on to be used as learning materials given by educators, so that students can open the files provided anytime and anywhere without having to meet or meet with educators. The research method used is a qualitative method, which uses a questionnaire to be given to 30 students where there are questions about students' opinions in using the classroom application. The research results obtained are where students can greatly improve student learning achievement, because it can help students in learning.